Nitrogen removal from landfill leachate using a sequential biological passive system (2013)
The efficiency of an anaerobic-aerobic biofilm passive system for nitrogen conversion was investigated. Leachate from real landfill is characterized by high ammonia content. Several techniques have been tested for ammonia nitrogen removal including air stripping, which imply high cost operation. In this work, an innovative design which combines a Bio- Reactive Permeable Barrier (BioBarrier) and multilayer Bio-trickling Reactor (BtR) was evaluated for nitrogen removal. The results show an excellent performance of BtR system, in which concentration of NO3 raise from 100±10 mg/L NO3 to near 1000±100 mg/L NO3. Almost 95% NH4 removal was observed, demonstrating efficiency of this device. However, N dynamics in BRPB had no important changes, probably due to low biofilm content of the package material. The BtR system was designed to promote O2 transference from the atmosphere without external energy input. Results confirm feasibility of nitrification process within tower. From the experimental data it can be concluded that BtR system is an efficient and economical system for ammonia removal, making it an innovative and potential system for small communities.